The effect of audit committee and board of directors characteristics' on audit fees and internal control quality in Iran; El efecto de las características del comité de auditoría y de la junta directiva sobre los honorarios de auditoría y la calidad - Mahdi Salehi; Noman Rashidi Soorestani (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2019)
This study investigates the effect of characteristics of board of directors and audit committee strength on audit fees internal control quality. In this study, 84 companies listed on the Tehran Stock Exchange were evaluated from 2014 to 2016. Panel regres sion model and panel logistic regression model were used for testing hypotheses related to audit fees and the weaknesses of internal control quality, respectively. Results showed that there is no significant relationship between the authority of board of directors and audit committee and the independence board and audit committee expertise and internal control quality weakness and also between the board power and audit fees. There is a significant relationship, however, between the board independence and audit committee authority, expertise, as well as the audit fees. Furthermore, results indicated that there is no significant relationship between board effort and audit fees and internal control quality weakness.
Keywords: D21; G32; L21; 330; audit fees; internal control quality; board of director; audit committee